Peran Nyai Dalam Pengembangan Ekonomi Pondok Pesantren Nurut Taqwa Dusun Duku Desa Sungairujing Kecamatan Sangkapura Kabupaten Gresik Jawa Timur - Nurdiana, Defi Dachlian; Awaliyah, Ana Luthfia Putri (CENDEKIA: Jurnal Studi Keislaman, 2021)
in the development of the Nurut Taqwa Islamic boarding school, Nyai also has a special role in the economic development of the Nurut Taqwa Islamic boarding school. This research method is qualitative. The results of the study (1) Nyai in Islamic boarding schools have a dual role, namely the domestic role and the public role. Nyai's role as a manajer at the Kopontren Nurut Taqwa plays a role in planning, coordinating, and evaluating everything related to the Kopontren. (2) The strategy carried out instills a sense of trust and honesty so that the Kopontren management does not feel pressured. (3) the problems that occur in the kopontren are the lack of capital, many students are in debt, and the management's lack of knowledge about cooperatives.